STRATEGI DA’WAH IKATAN DA’I KABUPATEN LOMBOK UTARA IKAD KLU DALAM MENINGKATKAN NILAI-NILAI KEISLAMAN DI PEDALAMAN LOMBOK UTARA NTB - Madeni Madeni; Ritajib (Jurnal Bina Ummat: Membina dan Membentengi Ummat, 2020)
Abstract: Da’wah society be union da’i regency north Lombok in increase the value Islamic at community villags north Lombok? How pormulation strategy from society be union da’i regency north Lombok in increase the value Islamic? How implementation strategy da’wah society be union da’i regency north Lombok? And how respons from community connected da’wah society be union da’i north Lombok? In this thesis research, the author uses descriptive qualitative research methods, namely by understanding the about experienced by the research subects such as behaviour, perception, motivation and action. Deskriptive research methods a process of finding facts images or between the phenomena under study. As for the technique of collecting data using observation, interviews and documentation. Strategy da’wah in the society be union da’i regency north Lombok with all sorts of strategy such as make to innefektive to university for free, the contract in Masjid and participate to community in the villags and inside to strengthen economy and the finish problems.